Strategi kepemimpinan siswa melalui public speaking sebagai sarana pengembangan bakat di SMAN 2 Banguntapan - Hodiri Adi Putra; Nor Wijayanti (Buletin Pengabdian Multidisiplin, 2024)
Purpose − One of the supporting competencies of leadership is public speaking for students. Public speaking skills are still not fully possessed by students. Low self-confidence, and minimal mastery of public speaking techniques are factors in students' reluctance to appear in public. This community service activity aims to conduct socialization and training on the application of student leadership strategies through public speaking as a means of developing talent at SMA Negeri 2 Banguntapan. Method − The stages of this community service activity begin with preparation in the form of permission from partners, agreement on the implementation time, checking supporting equipment such as projectors, LCDs, etc. Socialization and training on student leadership and public speaking with 35 students Findings − After carrying out community service activities in the form of socialization and training on the application of student leadership strategies through public speaking as a means of developing talent at SMA Negeri 2 Banguntapan, also through pre-tests and post-tests, it resulted in better student understanding and skills about leadership and public speaking.